Fenomena Anti-fans pada Transformasi Persona Selebriti Sam Smith di Media Sosial - Aini, Syarifah Nur; Akalili, Awanis; A’yun, Bintan Auliya Qurrota (Universitas Al Azhar Indonesia, 2025)
Sam Smith seems to be active in appearing to show his feminine aspects since he declared himself non-binary in 2019. Sam Smith has become increasingly brave to be open as a queer individual and shows confidence with his body. Even Sam Smith wore clothes that the public considered strange and revealing, causing various controversies in conservative circles. The purpose of this research is to determine the form of anti-fans that occurred regarding the transformation of celebrity Sam Smith's persona. Through a qualitative approach, it was found that the public who did not like Sam Smith's personal appearance tended to be active in providing negative comments on photo and video uploads on Sam Smith's personal Instagram social media account, namely @samsmith. In the comments by anti-fans, there are visible attempts to insult, use harsh words to demean, give emoticons and memes to represent negative emotions.